2013
DOI: 10.1002/mds.25365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of placebo assignment in clinical trials of tic disorders

Abstract: The magnitude of the placebo effect in tic disorders appeared to be small. Further longitudinal studies using objective assessments for tic disorders are warranted to confirm the current results. © 2013 Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…There is one systematic review in tic disorders that only evaluated the placebo response and not the nocebo response . This study included six placebo‐controlled RCTs (parallel and cross‐over study designs), assessing medical interventions for tic disorders (literature search from 1990 until 2008) in a total of 91 patients included in placebo arms.…”
Section: Resultsmentioning
confidence: 99%
“…There is one systematic review in tic disorders that only evaluated the placebo response and not the nocebo response . This study included six placebo‐controlled RCTs (parallel and cross‐over study designs), assessing medical interventions for tic disorders (literature search from 1990 until 2008) in a total of 91 patients included in placebo arms.…”
Section: Resultsmentioning
confidence: 99%
“…Marked reductions in Unified Parkinson Disease Rating Scale scores can be seen up to 6 months from the application of placebo . As a result of these studies, a cutoff of 50% improvement in symptoms has been regarded as the standard for placebo response in other movement disorders, including progressive supranuclear palsy, Huntington's disease (HD), and tic disorders . FXTAS includes parkinsonism as a motor feature and could reasonably be added to the list of movement disorders to hold to this standard.…”
Section: Discussionmentioning
confidence: 99%
“…15 As a result of these studies, a cutoff of 50% improvement in symptoms has been regarded as the standard for placebo response in other movement disorders, including progressive supranuclear palsy, 16 Huntington's disease (HD), 18 and tic disorders. 19 FXTAS includes parkinsonism as a motor feature and could reasonably be added to the list of movement disorders to hold to this standard. However, the neuropsychiatric profiles of PD and FXTAS are quite different, with cognitive impairment occurring earlier in the disease course and characterized by more prominent executive dysfunction in FXTAS than in PD.…”
Section: Discussionmentioning
confidence: 99%
“…al, who demonstrated that the magnitude of improvement resulting from placebo effect was relatively small (0.16 for all participants, 0.18 for children), but clinically relevant. 42 The etiology of this effect remains unclear; with suggestions including observer bias, inaccuracy of self-assessment of tic severity, or the fluctuating nature of tics. The magnitude of improvement seen in our small placebo group was larger than that typically described.…”
Section: Discussionmentioning
confidence: 99%